2020
DOI: 10.3390/ph13040062
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fast Nerve Conduction Produced by Analgesics and Analgesic Adjuvants—Possible Involvement in Pain Alleviation

Abstract: Nociceptive information is transmitted from the periphery to the cerebral cortex mainly by action potential (AP) conduction in nerve fibers and chemical transmission at synapses. Although this nociceptive transmission is largely inhibited at synapses by analgesics and their adjuvants, it is possible that the antinociceptive drugs inhibit nerve AP conduction, contributing to their antinociceptive effects. Many of the drugs are reported to inhibit the nerve conduction of AP and voltage-gated Na+ and K+ channels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 271 publications
(445 reference statements)
0
15
0
Order By: Relevance
“…Whether and to what extent the Nav blockade of these drugs is responsible for their analgesic effect observed in humans remain unclear. In vitro opioid studies examining morphine, tramadol, fentanyl, sufentanil, and buprenorphine showed a decrease in action potential amplitudes and conduction via direct action on Nav and Kv channels in frog sciatic nerves [ 138 ], and on unmyelinated mouse C-fibers [ 139 ]. Moreover, loperamide inhibited Nav1.7 and Nav1.8 as well in an in vitro study [ 140 ].…”
Section: Molecular/cellular Mechanisms Of Topical Treatments In Patients With Localized Neuropathic Painmentioning
confidence: 99%
See 3 more Smart Citations
“…Whether and to what extent the Nav blockade of these drugs is responsible for their analgesic effect observed in humans remain unclear. In vitro opioid studies examining morphine, tramadol, fentanyl, sufentanil, and buprenorphine showed a decrease in action potential amplitudes and conduction via direct action on Nav and Kv channels in frog sciatic nerves [ 138 ], and on unmyelinated mouse C-fibers [ 139 ]. Moreover, loperamide inhibited Nav1.7 and Nav1.8 as well in an in vitro study [ 140 ].…”
Section: Molecular/cellular Mechanisms Of Topical Treatments In Patients With Localized Neuropathic Painmentioning
confidence: 99%
“…NSAIDs such as diclofenac, aceclofenac, indomethacin, tolfenamic, and flufenamic acid reduced action potential amplitudes and inhibited nerve conduction through Nav inhibition in frog sciatic nerves in a concentration-dependent manner, probably due to their chemical structure being similar to local anesthetics [ 138 ]. A similar inhibitory effect on the action potential was observed after application of clonidine (α2-AR agonist) on frog sciatic nerves, which was attributed to Nav blockade [ 138 ]. Moreover, ketamine was shown to directly inhibit Nav in neuroblastoma cells [ 141 ], which may account for the analgesic effect of ketamine as adjuvant to local anesthetic agents.…”
Section: Molecular/cellular Mechanisms Of Topical Treatments In Patients With Localized Neuropathic Painmentioning
confidence: 99%
See 2 more Smart Citations
“…In clinical studies conducted in patients with PHN specific blocker of Nav1.7 (TV-45070) has been assessed as well, but no statistical difference was observed between active treatment and placebo for the change in mean daily pain scores from baseline compared with the last week [122] Other substances being suggested to exert their antinociceptive effect via Nav blockade in vitro in peripheral nerves include NSAIDs, opioids, α2-AR agonists, and plant-derived compounds, which has been extensively reviewed by Kumamoto [123].…”
Section: Treatments Acting On Voltage-gated Sodium Channelsmentioning
confidence: 99%